Comportamento de tamanduá-mirim, Tamandua tetradactyla (Linnaeus,1758) (Pilosa, Myrmecophagidae) em condições de cativeiro: implicações ao bem-estar - Catapani, Mariana Labão (Universidade Federal de São Carlos, 2014)
Modern zoos have an important role to play in conservation and there is a growing concern for animal welfare, not only by the expectation of the public , but also by increasing knowledge about the needs of animals in captivity . Increase the available alternatives of choice for the animal, the richness of his social life , the availability of new items in the room, the opportunities it has to perform more natural behaviors for the species are some of the strategies that are assumed to promote high levels welfare ( Young, 2003) .In this context, environmental enrichment techniques are developed . The social enrichment is one of the most durable types of enrichment, since the predictability and habituation are less likely to happen than with most other types of enrichment. The social environment of many species is a constant source of mental stimulation, with a complex and hard to be replaced by any other form of environmental enrichment ( Humphrey , 1976) variety. Thus, a factor considered important for the welfare of captive social animals is the presence of conspecifics sharing the same enclosure, but the social housing solitary species has received little attention from scientists in terms of their implications for the welfare. This study investigated the effect of different conditions of social housing on the behavior s display for 10 lesser anteaters ( Tamandua tetradactyla ) on captivity. It was found that paired animals were more active, showed more records of typical behavior and a greater variety of behaviors than the animals housed individually. These results suggest that contact with conspecifics in captive conditions can promote higher levels of psychological well -being for these animals.
Keywords: Conservação; Alojamento social; Bem-estar animal; Animais selvagens em cativeiro; Animais - comportamento; Tamanduá-mirim; CIENCIAS BIOLOGICAS::ECOLOGIA